Further changes in the areas of stray bird species of the Eastern Siberia recorded in the first half of the 20th century - Mel’nikov Yuriy (E3S Web of Conferences)
Based on the literature and our own materials, the features of the settlement in Eastern Siberia of 60 species of stray birds that appeared here in the first half of the 20th century were analyzed. It has been shown that many birds classified as vagrant species are not actually vagrant. Most of them end up in new regions due to errors in navigation or as a result of being blown by strong winds. Some species are considered vagrants due to their rarity or very low numbers along their migration routes. It has been proven that the development of new territories is carried out using three types of settlement: gradual development of adjacent areas (“frontal offensive”), long-distance invasions with further slow growth in numbers from a few foci, and mass invasion followed by rapid seizure of territory. It was found that the number of bird species settling to the east and west in the first half of the 20th century was approximately the same. It is shown that only 28 bird species (46.6%) out of 60 actually responded to the initial, albeit weakly expressed, climate warming by expanding their areas, 22 species (36.7%) accidentally ended up in Eastern Siberia, and 10 species (16.7%) belong to very few and rare migratory birds. Mass invasion followed by rapid development of the territory is the rarest event. It has been proven that such cases are most typical for birds of shallow-water and swampy ecosystems.